Vacuumless kink systems from vacuum systems: An example - Dutra, Alvaro de Souza [UNESP]; de Faria, ACA (American Physical Soc, 2005)
Some years ago, Cho and Vilenkin, introduced a model which presents topological solutions, despite not having degenerate vacua as is usually expected. Here we present a new model with topological defects, connecting degenerate vacua but which in a certain limit recovers precisely the one proposed originally by Cho and Vilenkin. In other words, we found a kind of parent model for the so called vacuumless model. Then the idea is extended to a model recently introduced by Bazeia et al. Finally, we trace some comments the case of the Liouville model.